PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUKMENINGKATKAN HASIL BELAJAR IPS KELAS III.BSD NEGERI 161 PEKANBARU - Herlinawati Herlinawati; Zariul Antosa; Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problems underlying is the low result graders social studies III.B SD Negeri 161 Pekanbaru. This is caused by the applied learning model the teacher has not been able to engage students actively in the learning process, the media used by teachers less varied, less teachers provide concrete examples to students, teachers only provide information and expect students to memorize and remember. This research aims to improve student learning outcomes IPS SD Negeri 161 Pekanbaru class III.B academic year 2014/2015 through the implementation of cooperative learning model Group Investigation (GI) by the number of students 39 people, consisting of 23 male students and 16 female students. This research is a form of action research. The research instrument consists of learning tools and data collection instruments such as teacher observation sheet activities, student activities, and the test results of students' social studies class III.B SD 161 Pekanbaru. Improved learning outcomes can be determined from the average yield of the study before action is preliminary data 64.85, daily test-1 80.26, daily Deuteronomy-2 85.77. From the initial data to the UH-1 increased by 15.41 percentage points to 23.76%, and the increase in the initial data for the UH-II rise again as much as 20.92 percentage points to 32.26%, From the above we can see that the results learning increases. With the learning outcomes in classical completeness reached 85.77% and in classical learning outcomes IPS graders SD Negeri 161 Pekanbaru III.B can be said complete.Keywords: cooperative model GI type, Improving Learning Achivement IPS